2021
DOI: 10.1039/d0ra09323h
|View full text |Cite
|
Sign up to set email alerts
|

Propionamide participating in H2SO4-based new particle formation: a theory study

Abstract: Propionamide (PA), an important pollutant emitted into the atmosphere from a variety of sources, is abundant in many areas worldwide, and could be involved in new particle formation (NPF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The NPF capability of SA with amides is found to be greater than with the studied organic acids. This is consistent with the studies by Ma et al 238 and Zhao et al, 239 that amides bind stronger with SA than AM but in most cases weaker than the common alkyl-amines (e.g., MA and DMA). Considering the high atmospheric concentration of amides they are likely to play an important role in atmospheric NPF.…”
Section: Amidessupporting
confidence: 93%
See 1 more Smart Citation
“…The NPF capability of SA with amides is found to be greater than with the studied organic acids. This is consistent with the studies by Ma et al 238 and Zhao et al, 239 that amides bind stronger with SA than AM but in most cases weaker than the common alkyl-amines (e.g., MA and DMA). Considering the high atmospheric concentration of amides they are likely to play an important role in atmospheric NPF.…”
Section: Amidessupporting
confidence: 93%
“…They showed that amides bind relatively strongly to SA (with ΔG from 4.42 to 10.46 kcal/mol), and thus they bind stronger than AM and some even have the same capability of DMA (e.g., trans ‐ N ‐methylacetamide). Zhao et al 239 examined the (propionamide) 0–3 (SA) 0–3 cluster system. It was shown that ppb concentrations of propionamide could enhance NPF but still less than bases such as MA or DMA.…”
Section: Cluster Formation Studiesmentioning
confidence: 99%
“…As a kind of volatile nitrogen-containing organic compounds widely existing in the atmosphere, amides play a key role in the synthesis of cosmetic products, polymers, and drugs . The animal husbandry, biomass burning, industrial, and agricultural production processes are all its main emission sources; the gaseous amides have been found near these sources, which can reach the parts per billion by volume (ppbv) level in urban Shanghai, China. At the same time, urea has been detected as one of the important components of water-soluble organic nitrogen fractions constituted the major part of the fine aerosol particles, and it has a variety of natural and artificial sources, , which has been discovered in aqueous aerosols and rainwater. , In areas with typical C 3 -amides concentration, propionamide can increase the H 2 SO 4 -based NPF at the ppb level . Other studies have also shown that amide molecules including urea can stabilize H 2 SO 4 and may promote NPF. , Urea and glutaric acid (GA) molecules can form the clusters synergistically, and its stabilizing effect on GA is stronger than that of aliphatic amines, such as methylamine (MA) and dimethylamine (DMA) …”
Section: Introductionmentioning
confidence: 99%
“…21,22 In areas with typical C 3 -amides concentration, propionamide can increase the H 2 SO 4 -based NPF at the ppb level. 23 Other studies have also shown that amide molecules including urea can stabilize H 2 SO 4 and may promote NPF. 24,25 Urea and glutaric acid (GA) molecules can form the clusters synergistically, and its stabilizing effect on GA is stronger than that of aliphatic amines, such as methylamine (MA) and dimethylamine (DMA).…”
Section: Introductionmentioning
confidence: 99%